Функціонування лексичних та фразеологічних одиниць у староукраїнських ділових текстах (на матеріалі «Актів (протоколів) Полтавського міського уряду кін. XVІІ – поч. XVIII ст.») - Штанденко, У. (Лексикографічний бюлетень, 2011)
The article on the material «Аcts (protocols) Poltava city government» considers the specific text of the office in the end XVII – the beginnings of XVIII centuries, describes the structure and content of contemporary business documents filed characterizing the living language elements of that time, the peculiarities of old Ukrainian lexical and phraseological structures found in the studied texts, that reflect sources of colloquial speech of that time.